2020
DOI: 10.1080/23311886.2020.1807111
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the heuristic traps paradigm in avalanche education: Past, present and future

Abstract: This paper will review the emergence and adoption of decision heuristics as a conceptual framework within the avalanche research and education community and demonstrate how this emphasis on the heuristic decision framework has anchored and was critical in redefining the discussion around avalanche accidents. This paradigm has been a critical and meaningful step in recognizing the importance of decision making in avalanche accidents. However, in an attempt to reduce the incidence of fatal accidents, the adoptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…Our research found no evidence that sunny versus cloudy skies influenced liking or perceived safety. These findings are applicable for the ongoing evaluation of the heuristic traps conceptual framework and its relevance for avalanche risk management strategies, tools and education (see Johnson et al 2020). We recognize, however, that the task of judging avalanche risk may have focused participants' attention on risk to a greater degree than it would be in a natural situation.…”
Section: Do Skiers' Preferences Influence Their Perception Of Risk?mentioning
confidence: 84%
See 1 more Smart Citation
“…Our research found no evidence that sunny versus cloudy skies influenced liking or perceived safety. These findings are applicable for the ongoing evaluation of the heuristic traps conceptual framework and its relevance for avalanche risk management strategies, tools and education (see Johnson et al 2020). We recognize, however, that the task of judging avalanche risk may have focused participants' attention on risk to a greater degree than it would be in a natural situation.…”
Section: Do Skiers' Preferences Influence Their Perception Of Risk?mentioning
confidence: 84%
“…Nonetheless, those failed manipulations are relevant for the field of avalanche research and education. For the past two decades, a focus on erroneous decision heuristics (referred to as heuristic traps) has dominated examinations into the decision processes that result in avalanche accidents and fatalities (Johnson et al 2020). One of the heuristic traps specified in that conceptual framework is the scarcity heuristic.…”
Section: Do Skiers' Preferences Influence Their Perception Of Risk?mentioning
confidence: 99%
“…Unfortunately, the experience of avalanche terrain appears to lead many backcountry skiers to make such mistaken assumptions. Avalanche terrain is a decision environment in which poor decisions are infrequently marked by valid feedback (Ebert, 2019;Johnson et al, 2020;Zweifel & Haegeli, 2014). Valid feedback is essential for the experiential learning and calibration process (Fischer & Budescu, 2005;Hogarth et al, 2015;Sanchez & Dunning, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating the relationship between physiology and behaviour is difficult. Moreover, our behaviour in extreme environments results not just from our acute brain state, but a complex interplay of heuristics, informed by environmental and social cues (Johnson et al, 2020).…”
Section: From Pigeon Holes To Descending Spirals: a Paradigm Of Physiology Cognitive Performance And Behaviour In Extreme Environmentsmentioning
confidence: 99%
“…Investigating the relationship between physiology and behaviour is difficult. Moreover, our behaviour in extreme environments results not just from our acute brain state, but a complex interplay of heuristics, informed by environmental and social cues (Johnson, 2020). The paradigm is a first step at attempting to propose a potential pathway, or mechanism, responsible for these observations in an otherwise largely descriptive body of literature.…”
mentioning
confidence: 99%